Do experienced physiotherapists and final year physiotherapy trainees apply similar force during posterior-to-anterior lumbar mobilization techniques?. (February 2016) - Gagnon, Dany H.; Longtin, Christian; Berbiche, Djamal; Gaudreault, Nathaly
Abstract: This study aims to quantify the force applied during posterior-to-anterior lumbar vertebrae mobilizations of different grades (I to IV) and compare that force between experienced physiotherapists and final year physiotherapy students. Four experienced physiotherapists and four final year physiotherapy students participated in this study along with five healthy asymptomatic individuals. A manual therapy table positioned over three force plates allowed for measurements of the force oscillation frequency and intensity applied during grade I, II, III and IV posterior-to-anterior (PA) mobilizations at two lumbar vertebral levels (L2 and L4). Mixed model ANOVAs were used to compare the force applied between the experienced physiotherapists and students, and between the various grades. The results showed that the mean oscillation frequency was similar between the groups for all grades. Grade I and grade IV PA mobilizations showed similar mean oscillation frequency as did grade II and III PA mobilizations. The minimum and maximum force applied was higher for the physiotherapists than for the students for all mobilization grades ( p values < 0.05). Similar mean maximum force values were recorded for PA mobilizations between grade I and II and between grade III and grade IV. Grade III and IV PA mobilizations yielded higher mean maximum force values than those recorded during grade I and grade II PA mobilizations. The method used in this study allowed for quantification of the force applied during lumbar PA mobilizations. Experienced physiotherapists apply greater force than physiotherapy students across all grades, despite similar oscillation frequency. Highlights: Force magnitude allowed for differentiation across all lumbar PA mobilization grades. Physiotherapists apply greater force than physiotherapy students across all grades. This difference warrants consideration when teaching spinal manipulative therapy.